Trans isomers of unsaturated fatty acids increase the risk of atherosclerosis-related circulatory system diseases - N V Perova; V A Metel'skaia; S A Boĭtsov (Терапевтический архив, 2013)
The paper provides a review of the literature on a relevant non-drug prevention problem, namely the negative effect of trans isomers of unsaturated fatty acids (trans-UFA) on the risk of circulatory system diseases (CSD) and other chronic noncommunicable diseases. It gives data on the specific features of the structure and ability of trans-UFA to elevate the plasma levels of atherogenic low-density lipoproteins and to lower those of non/antiatherogenic high-density lipoproteins. The natural sources of their moderate content in the animal fats from ruminants and those of their redundant content in the margarines manufactured by hydrogenation of liquid vegetable oils are described. A new technology for preparing soft margarines (spreads) is presented, which can produce fatty products that do not virtually contain trans-UFA. There is evidence that trans-UFA can considerably raise the risk of CSD and their acute complications. It is concluded that the manufacture of fatty products with low and even no trans-UFA levels should be expanded in Russia to improve its population's health.